Hubungan Rinitis Alergi dengan Kejadian Asma Bronkial - Dinni Istiqomah; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2023)
Allergic rhinitis is a risk factor for asthma. The development of asthma is generally more common in patients with allergic rhinitis. This is in accordance with epidemiological data which states that there has been an increase in cases of allergic rhinitis accompanied by asthma globally. Allergic rhinitis and asthma are both mediated by Immunoglobulin E (IgE). The correlation between nasal airflow obstruction in allergic rhinitis sufferers and lung airflow obstruction due to the inflammatory process that occurs in the nasal mucosa of allergic rhinitis and asthma sufferers can be determined by observing the nasal airflow and bronchial airflow. The diagnosis of asthma can be known by measuring the Forced Expiratory Volume in One Second Percent (FEV1%) value. In allergic rhinitis patients, a decrease in FEV1% was found and reversibility was found after a bronchodilator test. Such reversibility is associated with long duration (chronic) allergic rhinitis and early bronchial airflow limitation. This 1% decrease in FEV and reversibility suggest the presence of BHR, especially in persistent and moderate-severe allergic rhinitis patients. Duration and type of sensitization (allergen) were identified as early prognostic markers of BHR involvement in allergic rhinitis patients. Knowing the FEV1% value in allergic rhinitis sufferers is expected to be a preventive measure for the occurrence of asthma.